Experimental analysis of the electromagnetic damper of a non-ideal system revisited - Petrocino, E. A. [UNESP]; Balthazar, J. M. [UNESP]; Gonçalves, P. J.P. [UNESP]; Silveira, M. [UNESP]; Tusset, A. M. [UNESP]; Ribeiro, M. A. (IOP Publishing, 2024)
The use of limited power motors fixed to flexible structures is widely used in engineering and has seen a significant increase in published studies. These components form a non-ideal system, which can cause undesirable phenomena throughout its execution, such as the capture of parametric oscillation by resonance, studied by Sommerfeld, whose effect bears his name. One study, on a vibration absorber in a non-ideal system, was done in Petrocino et al., Meccanica, v. 58, n. 1, p. 287-302, 2023, on a model that represents a fixed beam and at the free end a motor with its unbalanced shaft. In this work, based on the equations that govern the movement, an analytical development was carried out, using the average method, to obtain an approximate solution and numerical simulations with the absorber on and off. The results demonstrated a reduction in parametric excitation, an effect caused by the electromagnetic absorber. Based on the parameters of this revisited work, a prototype was built to carry out experimental tests. A beam was fixed at one end and at the free end a DC motor was fixed with an unbalance on its axis, a magnet fixed at the free end immersed in the core of a coil as a damping actuator. When the motor is accelerated, it causes a parametric excitation in the beam and is captured by resonance, where the damping action is evident. The results of the tests were compared with the results of the models from the revisited work, validating the performance of the passive electromagnetic vibration absorber.
Keywords: Electromagnetic vibration damper; Non-ideal systems; Resonance capture...